(untitled) (International Journal of Engineering and Computer Science, 2017)
“Data transfer through power line is a technology that sends data through Electric line along with electric current. In this we study data transmission applicability over power lines for home automation. This study concluded after the problem defined by previous research. Two major problems such as cable attenuation and excessive noise level are eliminated by our project. We designed this technology in two phases, in first phase, run the performance analysis of this technology. And secondly, build system that represents the real life applications with security issues. In data transfer through power line we transmit the eight bit command through 230volt and 50Hz supply. This project provides large coverage, since the power lines are already installed everywhere.”